The mediating role of self-efficacy between parent-child attachment and romantic relationship among undergraduate students in Malaysia - Beh, Zye Han; Hiew, Yi Xin; Koh, Olivia Shu Qi (2022)
The attachment styles have a significant influence on the development of children's interpersonal concepts, which would impact the quality of intimate relationships. There are only a few attempts have been undertaken to examine the connection between attachment type and romantic relationship involvement in Malaysia. Thus, the goal of this study is to examine the relationship between self-efficacy, parent-child attachment and romantic relationship. This study used quantitative research design to collect and analyze data. A total number of 138 participants were recruited through purposive sampling on social media platform such as Microsoft Team, WhatsApp, Instagram and Facebook. The data was collected through online using Qualtrics questionnaire survey form. All of the 138 participants completed the survey and fulfilled the criteria of (i) one must be a Malaysian undergraduate student currently enrolled in either Malaysian university, (ii) one must be between the ages of 19 to 25 and (iii) one must be engaging in a romantic relationship. Inventory of Parent and Peer Attachment – Revised (IPPA – R), Relationship Involvement Scale (RIS) and New General Self-Efficacy Scale (NGSE) were used to examine the desirable variables. Before distributing the questionnaire for the pilot study, numerous ethical issues should be addressed in order to properly administer the research. Malaysian undergraduates who met the requirements were sent an online questionnaire created using Qualtrics through online platform such as WhatsApp, Microsoft Team, Instagram and Facebook. The questionnaire includes an informed consent page at the beginning to ensure that respondents understand that their participation is entirely voluntary and that their responses will be kept confidential, after getting their consent, they can start proceeding with the questionnaires. Pearson correlation showed that there was a non-significant and positive relationship between parent child attachment and romantic relationship among undergraduates’ students in Malaysia (r SELF-EFFICACY, ATTACHMENT, ROMANTIC RELATIONSHIP